1, 2, 4‐Oxadiazole ring–containing pyridylpyrazole‐4‐carboxamides: Synthesis and evaluation as novel insecticides of the anthranilic diamide family. (13th February 2020) - Khallaf, Abdalla; Wang, Ping; Liu, Hui; Zhuo, Shuping; Zhu, Hongjun
Abstract: Herein, we describe the preparation of pyridylpyrazole‐4‐carboxamides containing a 1, 2, 4‐oxadiazole ring as novel anthranilic diamide derivatives and compare their insecticidal activities to that of chlorantraniliprole, a well‐established potent insecticide. Biological activity tests reveal that all compounds had good insecticidal activities, with the most potent species achieving diamondback moth ( Plutella xylostella ) mortalities of 100% and 57% at concentrations of 400 and 200 μg mL −1, respectively. Abstract :